Werken van Michiel De Swaen : 2. De Tooneelspelen - Huysmans, Camille; Sabbe, Maurits; Celen, V. (Antwerpen : De Sikkel, 1928)
Bibliotheek E. Anseele
Genummerd ex. 06
Nederlands
Meerdelige publicatie
Keywords: toneel